Psychosocial career pre-occupation and workplace friendship at the University of Cape Coast: do socio-demographic characteristics matter? - Isaac Tetteh Kwao; Emmanuel Essandoh; Dorothy Amfo-Antiri; Felix Kwame Opoku; Rebecca Dei Mensah (Cogent Business & Management)
The study controlled for the moderating influences of age, gender, and marital status among University of Cape Coast staff members. It empirically investigated the relationship between psychosocial career pre-occupation and friendship prevalence and opportunity. Two hundred and eighty-eight (288) University of Cape Coast working staff received structured questionnaires using the explanatory research design. The hypotheses were analyzed and tested using Smart PLS’s structural equation modeling. The study revealed that psychosocial career pre-occupation predicts some positive, statistically significant, but small changes in friendship opportunity and prevalence. Age range, gender, and married status are a few personal traits that did not moderate the predictive link between workplace friendships and psychosocial-career preoccupation. Based on these findings, employees should follow the guidelines for career establishment, work-life balance, and career adaptation. By doing so, they may strengthen their bonds with coworkers in terms of friendship prevalence and opportunities. Furthermore, the study demonstrated how psychosocial-career preoccupation explains the form of workplace friendships among employees in higher education contexts, notably a university and an emerging economy in sub-Saharan Africa, and it supports the social exchange theory.